2020
DOI: 10.1177/0033294120948226
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Symptoms of Eating-Disordered Behavior Among Female Adolescents

Abstract: Background Compared to males, female adolescents show greater concerns about their appearance, concerns related to their self-esteem. We explored the associations between self-esteem, body image and BMI as proxies for appearance, and eating-disordered behavior among adolescent females. Methods A total of 263 females (mean age:15.78 years) took part in this study. They completed questionnaires covering anthropometric characteristics, self-esteem, eating-disordered behavior, subjective physical activity levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…Regarding individual characteristics, self-esteem has been identified as an essential factor in the appearance of EDs symptoms (Shroff and Thompson, 2006;Baylan et al, 2009;Rodgers et al, 2014;Garrusi et al, 2016;Kaewpradub et al, 2017;Argydes et al, 2020;Mora et al, 2022;Beckers et al, 2023). Therefore, low self-esteem during adolescence showed a significant association with EDs for both genders (McCabe and Vincent, 2003;Altamirano et al, 2011;Gomes et al, 2015;Teixeira et al, 2016;Gan et al, 2018;Rosewall et al, 2018;Jones et al, 2020;Zamani et al, 2020;Cella et al, 2021;Ćorić et al, 2023). However, self-esteem was also a moderator between other characteristics and EDs, especially body dissatisfaction or attitudes toward the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding individual characteristics, self-esteem has been identified as an essential factor in the appearance of EDs symptoms (Shroff and Thompson, 2006;Baylan et al, 2009;Rodgers et al, 2014;Garrusi et al, 2016;Kaewpradub et al, 2017;Argydes et al, 2020;Mora et al, 2022;Beckers et al, 2023). Therefore, low self-esteem during adolescence showed a significant association with EDs for both genders (McCabe and Vincent, 2003;Altamirano et al, 2011;Gomes et al, 2015;Teixeira et al, 2016;Gan et al, 2018;Rosewall et al, 2018;Jones et al, 2020;Zamani et al, 2020;Cella et al, 2021;Ćorić et al, 2023). However, self-esteem was also a moderator between other characteristics and EDs, especially body dissatisfaction or attitudes toward the body.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies showed self-esteem as a predictive factor with a direct influence on EDs symptomatology. Adolescents with lower selfesteem scores were more likely to develop disordered eating behaviors (McCabe and Vincent, 2003;Altamirano et al, 2011;Gomes et al, 2015;Teixeira et al, 2016;Gan et al, 2018;Rosewall et al, 2018;Jones et al, 2020;Zamani et al, 2020;Cella et al, 2021;Mora et al, 2022;Beckers et al, 2023;Ćorić et al, 2023). In two studies analyzing the role of gender, self-esteem was a strong predictor of the onset EDs symptomatology in both women and men (McCabe and Vincent, 2003;Cella et al, 2021).…”
Section: Synthesis Of Primary Outcomesmentioning
confidence: 99%
“…Among the factors that can influence this practice in adolescents is the limitation of access due to the incompatibility of schedule and the fact that the activities offered by public policies sometimes do not meet the preferences of this public, which can make them unattractive [9][10] . In addition, personal and family behaviors, socioeconomic level 11 , low self-esteem, dissatisfaction with body image 12 , anxiety and depression 13 and the presence of eating disorders 14 are also factors that are considered influential regarding physical activity and that, sometimes, are subject to intervention by health teams.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, intercultural differences also emerge in terms of the interconnections among the influence of mass media, the pursuit of the ideal body image and physical activity, and patterns of self-esteem, age and lifestyle [ 26 ]. These factors show, inter alia, that adolescents, as compared to adult men, exhibit greater concerns regarding their appearance and fears related to self-esteem [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%